Metastatic Orbital Tumor From Breast Ductal Carcinoma With Neuroendocrine Differentiation Initially Presenting as Ocular Symptoms: A Case Report and Literature Review - Togashi, Keita; Nishitsuka, Koichi; Hayashi, Shion; Namba, Hiroyuki; Goto, Sakiko; Takeda, Yusuke; Suzuki, Shuhei; Kato, Tomoya; Yamada, Yuki; Konno, Eriko; Yoshioka, Takashi; Yamakawa, Mitsunori; et al. (Frontiers in Endocrinology, 2021)
Background: Orbital metastases from cancers of various organs can arise via the hematogenous route, and many originate from breast, prostate, and lung cancers. Such metastatic orbital tumors may be diagnosed before the primary tumor. We have encountered a case of breast ductal carcinoma with neuroendocrine differentiation that metastasized to the orbit and responded to chemotherapy, with improvement in visual function. Case Presentation: A woman in her fifties visited our ophthalmology department with a chief complaint of foreign body sensation and exophthalmos in her right eye. An elastic soft mass was palpated from the lateral orbit to the temporal region. A systemic examination revealed breast cancer and a metastatic orbital tumor. Excisional biopsy of the breast revealed a diagnosis of invasive ductal carcinoma with neuroendocrine differentiation, and immunohistochemical examination was negative for cytokeratin 7, making the case unusual. Chemotherapy was remarkably effective, and the tumor size decreased, resulting in improvement of visual function. Her general condition and quality of life are still good at present. We searched the PubMed English language literature focusing on metastatic orbital tumors from breast cancer in which ocular symptoms had been the initial presenting sign. No previous reports have documented neuroendocrine differentiation or cytokeratin 7 expression in isolated orbital metastases from breast cancer. Although it is not possible to be certain from this case alone, we speculated that some such cases might involve cytokeratin 7-negative invasive breast cancer with neuroendocrine differentiation. Conclusion: We have described our experience of a very rare case of cytokeratin 7 negative breast ductal carcinoma with neuroendocrine differentiation that metastasized to the orbit and formed a solitary giant tumor initially manifesting as ocular symptoms.